Understanding the motivations, deterrents, and incentives for rural Albertan veterinary practice - Mughal, Hanna; O’Neill, Thomas A.; Le Huray, Lena; Bergman, Megan; Remnant, John; Galezowski, Angelica M.; Hecker, Kent G.; McCorkell, Robert (Frontiers in Veterinary Science, 2025)
IntroductionThe shortage of rural veterinarians is a growing concern globally. This shortage increases the risk of significant negative impacts on livestock management, agriculture, and public health in rural and remote communities. To provide concrete solutions to sustain our rural veterinarian workforce, we examine motivations, incentives, and deterrents to rural veterinary practice (RVP). We do this through a qualitative study in Alberta, Canada, which is a geographically unique and understudied context.MethodsWe surveyed veterinary students and practicing veterinarians, obtaining 124 responses. Data were analyzed using thematic analysis.ResultsResults revealed key motivating factors that influence attraction and retention included personal and family considerations that require living in rural contexts, the nature of strong relationships that develop in rural communities, experiencing a range in work factors that enhances professional development, feeling fulfilled by rural veterinary work, and exposure during veterinary school leading to a strong interest in rural settings. Deterrents included limited resources and supports in rural contexts, personal and family needs that require living in urban settings, and challenges inherent to rural communities and environmental characteristics. Finally, key incentives included better salary and benefits, financial incentives, tuition/debt forgiveness, enhanced mentorship, fewer on-call duties, and tailored incentives.DiscussionStrong alignment between student and practicing veterinarian motivations, deterrents, and incentives was observed, extending previous findings that only look at the perceptions of a single group. The results corroborated previous findings, while revealing that the same motivations and deterrents remained important for students and PVs in Alberta’s geographically unique context. Finally, they provided key insights to inform policy, practice, and education developments to enhance attraction and retention rates of rural veterinarians, contributing to a path forward for addressing the rural shortage of veterinary services.